Description and Comparative Genomics of Macrococcus caseolyticus subsp. hominis subsp. nov., Macrococcus goetzii sp. nov., Macrococcus epidermidis sp. nov., and Macrococcus bohemicus sp. nov., Novel Macrococci From Human Clinical Material With Virulence Potential and Suspected Uptake of Foreign DNA by Natural Transformation - Mašlaňová, Ivana; Wertheimer, Zuzana; Sedláček, Ivo; Švec, Pavel; Indráková, Adéla; Kovařovic, Vojtěch; Schumann, Peter; Spröer, Cathrin; Králová, Stanislava; Šedo, Ondrej; Krištofová, Lucie; Vrbovská, Veronika; et al. (Frontiers in Microbiology, 2018)
The genus Macrococcus is a close relative of the genus Staphylococcus. Whilst staphylococci are widespread as human pathogens, macrococci have not yet been reported from human clinical specimens. Here we investigated Gram-positive and catalase-positive cocci recovered from human clinical material and identified as Macrococcus sp. by a polyphasic taxonomic approach and by comparative genomics. Relevant phenotypic, genotypic and chemotaxonomic methods divided the analyzed strains into two separate clusters within the genus Macrococcus. Comparative genomics of four representative strains revealed enormous genome structural plasticity among the studied isolates. We hypothesize that high genomic variability is due to the presence of a com operon, which plays a key role in the natural transformation of bacilli and streptococci. The possible uptake of exogenous DNA by macrococci can contribute to a different mechanism of evolution from staphylococci, where phage-mediated horizontal gene transfer predominates. The described macrococcal genomes harbour novel plasmids, genomic islands and islets, as well as prophages. Capsule gene clusters, intracellular protease, and a fibronectin-binding protein enabling opportunistic pathogenesis were found in all four strains. Furthermore, the presence of a CRISPR-Cas system with 90 spacers in one of the sequenced genomes corresponds with the need to limit the burden of foreign DNA. The highly dynamic genomes could serve as a platform for the exchange of virulence and resistance factors, as was described for the methicillin resistance gene, which was found on the novel composite SCCmec-like element containing a unique mec gene complex that is considered to be one of the missing links in SCC evolution. The phenotypic, genotypic, chemotaxonomic and genomic results demonstrated that the analyzed strains represent one novel subspecies and three novel species of the genus Macrococcus, for which the names Macrococcus caseolyticus subsp. hominis subsp. nov. (type strain CCM 7927T = DSM 103682T), Macrococcus goetzii sp. nov. (type strain CCM 4927T = DSM 103683T), Macrococcus epidermidis sp. nov. (type strain CCM 7099T = DSM 103681T), and Macrococcus bohemicus sp. nov. (type strain CCM 7100T = DSM 103680T) are proposed. Moreover, a formal description of Macrococcus caseolyticus subsp. caseolyticus subsp. nov. and an emended description of the genus Macrococcus are provided.